CASE REPORT: FELINE INFECTIOUS PERITONITIS VIRUS IN MALE LOCAL CATS WITH ASCITES - Jayanti, Putu Devi; Gunawan, I Wayan Nico Fajar; Sulabda, Ni Luh Ayu Kartika Meidy Pramudiasari (Buletin Veteriner Udayana; Vol. 13 No. 2 Agustus 2021DO - 10.24843/bulvet.2021.v13.i02.p12, 2021)
Feline infectious peritonitis is a viral infection in cats with clinical signs of ascites occurring in the effusion form. Ascites are a common form of systemic state characterized by abdominal distention caused by fluid accumulation. A local cat aged 1year with a weight of 4 kg named Minmin came to Udayana University Animal Education Hospital with complaints of decreased appetite, weakness, difficulty defecation and abdominal cavity enlargement. On physical examination is known the presence of abdominal distension. For the edification of the diagnosis is carried out ultrasound examination, X-ray, and abdominocentesis. There is an accumulation of fluid in the abdominal cavity, hepatomegaly, and nephritis. Routine hematology and blood biochemical examinations are performed that indicate chronic inflammation and abnormalities in kidney function. Rivalta test results showed positive results of accumulated exudate characterized by jellyfish like formation. Therapy given in the form of diuretic administration furosemide 10 mg / ml intravenous injection with the amount of administration 0.45 ml (2 x daily), ornipural hepatoprotector subcutaneous injection with the amount of administration 2 ml (every 2 days), nephroprotektor ketosteril per oral with a total administration of 1/2 tablet (every 2 days), antibiotic cefotaxim sodium 1g/ml intravenous injection with a total administration of 1.3 ml (2 x daily), anti-inflammatory dexamethasone 5mg/ml subcutaneous injection with an amount of 0.4ml (2 x daily), and transfer factor 1 x 1 tablet for 7 days. The treatment provided gives good results against a decrease in the degree of abdominal distention.